Whole exome analysis identifies dominant COL4A1 mutations in patients with complex ocular phenotypes involving microphthalmia. (12th April 2014) - Deml, B.; Reis, L.M.; Maheshwari, M.; Griffis, C.; Bick, D.; Semina, E.V.
<x xml:space="preserve">Abstract</x> Anophthalmia/microphthalmia (A/M) is a developmental ocular malformation defined as complete absence or reduction in size of the eye. A/M is a heterogenous disorder with numerous causative genes identified; however, about half the cases lack a molecular diagnosis. We undertook whole exome sequencing in an A/M family with two affected siblings, two unaffected siblings, and unaffected parents; the ocular phenotype was isolated with only mild developmental delay/learning difficulties reported and a normal brain magnetic resonance imaging (MRI) in the proband at 16 months. No pathogenic mutations were identified in 71 known A/M genes. Further analysis identified a shared heterozygous mutation in COL4A1, c.2317G>A, p.(Gly773Arg) that was not seen in the unaffected parents and siblings. Analysis of 24 unrelated A/M exomes identified a novel c.2122G>A, p.(Gly708Arg) mutation in an additional patient with unilateral microphthalmia, bilateral microcornea and Peters anomaly; the mutation was absent in the unaffected mother and the unaffected father was not available. Mutations in COL4A1 have been linked to a spectrum of human disorders; the most consistent feature is cerebrovascular disease with variable ocular anomalies, kidney and muscle defects. This study expands the spectrum of COL4A1 phenotypes and indicates screening in patients with A/M regardless of MRI findings or presumed inheritance pattern.